Water Quality and Its Relation with Chlorophyll-a in Dry Season, in a Reservoir of Mediterranean Region - CEVIK, FATMA; BARIS DERICI, OSMAN; KOYUNCU, NURGUL; TUGYAN, CEM (Asian Journal of Chemistry, 2010)
This study was carried out between June 2004 and August 2004, in Seyhan dam, Adana, Turkey. This lake is under severe anthropogenic pressure and region has a typical Mediterranean climate. Water samples were taken weekly from two stations in littoral and pelagic zones. The temperature, pH and conductivity were measured by a CTD. Chlorophyll-a, NO2-N, NO3-N, NH4-N, SRP and SRSi were analyzed according to the standard methods. Differences among weeks for water quality variables were statistically significant (p < 0.01). Chlorophyll-a showed significant positive linear correlation with temperature, NH4-N and conductivity while NO2-N, NO3-N and TDS were inversely related (p <0.01). Results show that Seyhan dam has not yet reached the eutraphic stage. Consequently, more extensive studies are needed because the lake is thought to be the most changing site in region as a result of the increasing agricultural, aquacultural and human population. A water quality program should be established to conservation of lake quality.